The Effect of Teaching Methods and Learning Styles on Students’ English Achievement (An Experimental Study at Junior High School 1 Pasangkayu) - Syahrul Munir; Emzir Emzir; Aceng Rahmat (JETL (Journal of Education, Teaching and Learning), 2017)
The objectives of the research are to determine the effects of teaching methods (STAD and jigsaw) and learning styles (visual, auditory, and kinesthetic) on students’ English achievement. This research is an experimental study conducted at Junior High School Pasangkayu in 2014 with 213 sample which is selected stratified-randomly (n = 68). The results of the research are as follow: (1) English achievement of students taught with STAD is better than those of taught with jigsaw; (2) there is no significant difference in  English achievement among visual, auditory, and kinesthetic students; (3) there is any significant effect of interaction among teaching method and learning styles on students’ learning English achievement. The research also find out that for visual students, studying English achievement of students taught with STAD is better than that of students taught with jigsaw; for auditory students, learning English achievement  of students taught with jigsaw is better than that of students taught with STAD; and for kinesthetic students, English achievement of students taught with STAD is better than that of students taught with jigsaw. To sum up, STAD is more effective than jigsaw in improving students’ English achievement. STAD is suitable to improve English achievement of visual and kinesthetic students, and jigsaw is suitable to improve English achievement of auditory students.